Synthesis of Energetic Complexes [Co(en)(H2BTI)2]2 ⋅ en, [Cu2(en)2(HBTI)2]2 and Catalytic Study on Thermal Decomposition of Ammonium Perchlorate. Issue 7 (14th May 2019) - Liu, Jianchao; Qiu, Hao; Han, Jimin; Yang, Li
Abstract: A nitrogen‐rich compound 4, 5‐bis(1 H ‐tetrazol‐5‐yl)‐1 H ‐imidazole (H3 BTI) with high energy density has been reported as ligand to make metal‐organic energetic catalysts to improve the energy of catalysts for the first time. The high energetic catalysts [Co(en)(H2 BTI)2 ]2  ⋅ en and [Cu2 (en)2 (HBTI)2 ]2 were successfully synthesized and the structures of the complexes were confirmed by X‐ray single‐crystal diffraction. The catalytic effects of complexes on the thermal decomposition of ammonium perchlorate (AP) have been investigated separately by differential scanning calorimetry (DSC). The DSC results show that the AP can be completely decomposed at the temperature of 333.7 °C and 336.1 °C, respectively, which indicates that the pristine "two‐step" thermal decomposition of AP was transformed to a "one step" route upon addition of the copper catalysts. Besides the excellent catalytic performance of AP decomposition, the high energetic ligand Hn BTI can also release a large number of heats in the decomposition process, which can significantly enhance the total released heat of the mixture of AP. Abstract :